Deconstructing Generation Z's Self-Awareness through Problem-Solving Techniques in Group Guidance - Banu, Edigius Paulus; Indreswari, Henny; Bariyyah, Khairul; Kasa, Mark; Cantiga, Jaed Brian L. (Buletin Konseling Inovatif, 2025)
Self-awareness is an individual's ability to recognize their emotions, values, and thought patterns, as well as to understand factors that influence their actions and social interactions. Generation Z, growing up in the digital and information era, faces unique challenges due to their low awareness of mental health, leading to increased cases of anxiety, depression, and burnout resulting from social and academic pressures. Consequently, they are often trapped in self-unawareness and identity crises caused by contradictions between personal values and social expectations. This article aims to determine the extent of the use of problem-solving techniques in group guidance services over the past two years, evaluating their efficiency or inefficiency to assess whether deconstruction is needed. The method used in this article is qualitative research through a literature review. The literature review process involves: (1) gathering data from various sources, (2) processing relevant references, (3) presenting research findings, (4) abstraction, (5) interpreting results, and (6) drawing conclusions. The data sources are derived from reputable books and journals relevant to the study's topic. The findings indicate that using problem-solving techniques in group guidance services has been relatively effective and efficient in improving Generation Z's self-awareness. In conclusion, deconstructing self-awareness through problem-solving techniques in group guidance facilitates better self-awareness and unlocks the optimal potential for Generation Z's personal and social lives.